Analisis Kesiapan Komunikasi dan Elektronika Marinir Guna Meningkatkan Sistem Komunikasi Taktis Modern dalam Rangka Mendukung Operasi Amfibi - Didik Sutejo; Achmad Sochfan (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Amphibious operations represent one of the most complex military maneuvers, demanding high-precision coordination between land, sea, and air elements. The success of such operations is heavily dictated by the effectiveness of Tactical Communication Systems (TCS). This study aims to analyze the readiness level of the Marine Communication and Electronics (Komlek) units in facing the challenges of modern warfare and to formulate strategies for upgrading TCS capabilities. The research employs a descriptive qualitative method, evaluating three primary pillars: human resources (personnel), hardware infrastructure (materiel), and existing communication doctrines. Analysis reveals that while current field communication fundamentals remain functional, there is a critical urgency for technological modernization to mitigate Electronic Warfare (EW) threats, jamming attempts, and bandwidth limitations in difficult operational terrains. This article recommends a transition toward IP-based (Internet Protocol) communication systems, the strengthening of high-level data encryption, and the integration of military satellite communication systems to ensure continuity of Command and Control (C2). Enhancing communication readiness to be adaptive toward digital and cyber technologies is projected to increase the efficiency of real-time operational orders and intelligence reporting, ultimately bolstering the striking power and success rate of future Amphibious Operations.